Enhancement of Electromigration Reliability of Electroless-Plated Nanoscaled Copper Interconnects by Complete Encapsulation of a 1 nm-Thin Self-Assembled Monolayer. Issue 8 (1st August 2022) - Chen, Giin-Shan; Lee, Ching-En; Cheng, Yi-Lung; Fang, Jau-Shiung; Hsiao, Chien-Nan; Chen, Wei-Chun; Chang, Yiu-Hsiang; Pan, Yen-Chang; Lee, Wei; Su, Ting-Hsun
Abstract : The downsizing of integrated circuits for the upcoming technology nodes has brought attention to sub-2 nm thin organic/inorganic materials as an alternative to metallic barrier/capping layers for nanoscaled Cu interconnects. While self-assembled monolayers (SAMs) serving as the barrier materials for copper metalized films are well studied, electromigration (EM) of Cu interconnects encapsulated by SAMs is an untouched research topic. In this study, we report an all-wet encapsulating process involving SAM seeding/encapsulating and electroless narrow-gap filling to fabricate nanoscaled copper interconnects that are completely encapsulated by a 1 nm-thin amino-based SAM, subsequently annealed to some extents prior to EM testing. Both annealing and SAM encapsulation retard EM of the Cu interconnects tested at current densities on orders of 10 8 –10 9 A cm −2 . Particularly, SAM encapsulation quintuples the lifetime of, for example, as-fabricated Cu interconnects from 470 to 2, 890 s. Electromigration failure mechanisms are elucidated from analyses of activation energies and current-density scale factors obtained from the accelerated EM testing. The importance of SAM qualities (e.g., ordering and layered structure) as a prerequisite for the reliability enhancement cannot be overestimated, and the results of the SAM quality evaluation are presented. The mechanism of reliability enhancement is also thoroughly discussed.